Peacebuilding and the Arts
XXII, 483 p. 28 illus., 21 illus. in color.
Keywords: This volume explores the relationship between peacebuilding and the arts. Through a series of original essays the authors break new ground, setting out fresh ways of analysing how different art forms can contribute to the processes and practices of building peace. The book is divided into five sections (on Visual Arts, Music, Literature, Film and Theatre/Dance), with over 20 authors offering overviews of each art form, case studies from around the globe and critical reflections on how the arts can contribute to peacebuilding. By bringing together the insights of scholars and practitioners working at the intersection of these two broad fields, this book presents a series of unique, critical perspectives on the interaction of diverse art forms with a range of peacebuilding endeavours. Jolyon Mitchell is Professor and Director of CTPI at the University of Edinburgh, UK, where he specialises in Religion, Conflict and Peacebuilding with special reference to the Arts. Giselle Vincett is a sociologist of religion. Her work concentrates primarily on everyday performances of belief and on everyday and spatial experiences of deprivation in the West. Theodora Hawksley is a Roman Catholic theologian specialising in the area of peacebuilding and Catholic social teaching. She writes regularly on Ignatian spirituality. Hal Culberston is Associate Dean for Operations at the University of Notre Dame’s Keough School of Global Affairs. He specializes in NGO management, particularly in the peacebuilding context.